2012
DOI: 10.1166/jnn.2012.6785
|View full text |Cite
|
Sign up to set email alerts
|

Bulb-Shaped Field Emission Lamps Using Carbon Nano-Coil Cathodes

Abstract: Bulb-shaped field emission lamps (FELs) using carbon nano-coil (CNC) cathodes were fabricated and their performances were characterized. A straight steel wire grown with CNCs was placed on the symmetry axis in the bulb as the cathode. The anode was defined by a Ni film deposited on the bottom hemisphere of a 60-mm-diameter glass bulb. And a phosphor layer was coated on the Ni film for light generation via cathodoluminescence. A numerical simulation model for this geometry also was constructed. The simulated cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In recent years, several research teams, including us, have used CNCs as the cathode material to fabricate field emission lamp (FEL) devices [26,27]. The results of these previous studies have indicated that CNC cathode materials can effectively increase the lighting uniformity and light-spot density of FELs.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several research teams, including us, have used CNCs as the cathode material to fabricate field emission lamp (FEL) devices [26,27]. The results of these previous studies have indicated that CNC cathode materials can effectively increase the lighting uniformity and light-spot density of FELs.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with a CNT of the same length, a CNC has considerably more FE points [20,21]. In recent years, several research teams, including the present author's team, have used CNCs as the cathode material to fabricate FEL devices [22,23]. The results of these previous studies have indicated that CNC cathode materials can effectively increase lighting uniformity and light-spot density.…”
Section: Introductionmentioning
confidence: 89%
“…Additionally, CNCs are more robust than CNTs because the former are much thicker and thus can withstand a higher current density. Owing to their much larger diameter and higher FE site density, CNCs exhibit better long-term current emission stability, current density, FE efficiency, and lifetime than CNTs [18,19], and so they have already found application in FE lighting [38][39][40][41]. Consequently, CNCs are used as the emitter material in the X-ray tube in this work.…”
Section: Cncs As Electron Emitting Nanomaterialsmentioning
confidence: 99%